Preliminary Characterization of a Homogeneous Polysaccharide with Anticomplement Activity from Sijunzi Decoction - Ruijun Wang; Yunfei Ji; Ying Peng; Xiaobo Li (Journal of Chemistry)
Sijunzi decoction (SJZD) is a classical herbal prescription in traditional Chinese medicine (TCM) used for enhancing the function of immune system. In previous studies, a polysaccharide fraction S-3 was screened from SJZD by assessment of immune system regulation, intestinal microbiota, and SCFA in order to explore the immune active ingredients in SJZD. In the present study, S-3 was further purified, and a homogeneous polysaccharide S-3-1 with a molecular mass of 13.5 × 104 Da was obtained after further fractionation by Sephadex G-150 size-exclusion chromatography. The immunological activities of S-3-1 were assayed in vitro for the first time. The determination of the anticomplement activity showed that S-3-1 displayed inhibitory effects on classical pathway of the complement system, with CH50 values of 530 μg/mL. The FT-IR analysis showed that S-3-1 had absorptive peaks characteristic of polysaccharides. The methylation and GC-MS analysis showed that it is comprised of Rha, Ara, Xyl, Man, Gal, and Glc in a relative molar ratio of 0.35 : 0.37 : 1.4 : 0.31 : 3 : 0.8 and that it mainly contained 1,4-linked-Glc and 1,6-linked-Gal glycosidic bonds. The morphology of S-3-1 was observed by atomic force microscope (AFM). These results provided evidences for tracking the material basis of SJZD immune activity.